Digital Literacy-Based Learning in Islamic Education - Manal Hendawi; Saba Qadhi (CV. Zamron Pressindo, 2024)
The purpose this research is to explores the integration of digital literacy into Islamic education, highlighting its impact on enhancing the quality of learning and preparing students for the challenges of the digital era. The integration process involves teacher training, development of digital teaching materials, and the utilization of e-learning platforms. Despite challenges such as infrastructure limitations and resistance to change, opportunities abound, including increased access to diverse learning resources and the enhancement of critical thinking skills. The impact of digital literacy-based learning on Islamic education is significant, leading to enhanced critical thinking skills, improved access to resources, increased engagement and interaction, integration of Islamic values, and preparation for the digital age. By addressing challenges and leveraging opportunities, Islamic education can effectively integrate digital literacy, thus equipping students with the skills needed to succeed in today's digital world.